On the Bauschinger effect in TiAl alloys. (1st February 2016) - Paul, Jonathan D.H.; Hoppe, Roland; Appel, Fritz
Abstract: The Bauschinger effect has been investigated at room temperature on a multiphase titanium aluminide alloy based on γ(TiAl). The effect of strain reversal was assessed by comparing uni-directional tensile tests with those performed on specimens made from pre-compressed material. This deformation sequence has the advantage that both the forward and reverse parts of the Bauschinger cycle are in tension, i.e., they are not affected by non-axial deformation, buckling or specimen end constraint. The results suggest that no permanent softening develops upon strain reversal whereas significant transient softening is present. The effect seems to be caused by heterogeneities in the deformed state due to the multiphase constitution of the material. Graphical abstract: